Continuous glucose monitoring -- a novel approach to the determination of the glycaemic index of foods (DEGIF 1) -- determination of the glycaemic index of foods by means of the CGMS - Chlup, R; Jelenová, D; Kudlová, P; Chlupová, K; Bartek, J; Zapletalová, J; Langová, K; Chlupová, L (Experimental and clinical endocrinology & diabetes, 2006)
UNLABELLED: The glycaemic index (GI) is a measure of the food power to raise plasma glucose (PG) concentration after a meal. For its determination, classical methods register the development of glucose concentration in capillary plasma or whole blood. The aim of this prospective open-label trial was to compare the GI of selected foods obtained by means of the Continuous Glucose Monitoring System (CGMS) (Minimed Medtronic, Northridge, USA) which has not been applied for this purpose until now, with the respective GI determined by a conventional method using the Glucometer Advance System (GAS) (Hypoguard, Woodbridge, United Kingdom), and to assess the advantages of each approach. METHODS: Portions of tested foods containing 50 g of carbohydrates were eaten for breakfast and for dinner after 10 and 4 h fast, respectively, by 20 healthy volunteers. Using GAS, PG-curves were constructed from 9 PG values at time 0, 15, 30, 45, 60, 75, 90, 105 and 120 min after the meal, and, using CGMS, from 25 values of interstitial fluid glucose concentration (ISFG) stored within 120 min in 5-minute intervals in CGMS memory. The GI was calculated (for GAS and CGMS separately) by dividing the incremental area under the curve for the tested food by the average area of 3 tests performed with the standard. Having excluded tests with missing glucose values, there remained 285 GAS- and 290 CGMS tests for further analysis. In each volunteer, each food was tested 3 times within one week so that 1 to 3 GI's were obtained and averaged. The GI for each tested food was calculated as the mean from the respective average GI's of 20 volunteers. The GI-variability was assessed according to the respective SD. The preference of GAS vs. CGMS in the persons tested was explored by means of a questionnaire. MS Excel and the statistical program SPSS v. 10.1 were used to analyze the data. RESULTS: The GI values (mean +/- SD) measured by GAS/CGMS were for dark chocolate 43.6 +/- 22.13 %/44.0 +/- 21.71 % (p > 0.01); for apple baby food 46.1 +/- 21.38 %/53.8 +/- 37.69 % (p > 0.01); for puffed rice squares 76.5 +/- 20.24 %/76.9 +/- 27.62 % (p > 0.01); for yogurt 43.2 +/- 20.17 %/37.7 +/- 21.55 % (p > 0.01). The GI's of dark chocolate, apple baby food and yogurt, determined by either method, were significantly lower than the GI of puffed rice squares (p < 0.01). CGMS was preferred by 12 of 20 volunteers (60 %). CONCLUSIONS: No significant difference could be seen between the GI's determined by conventional method (GAS) and by CGMS (p > 0.01). The method with CGMS is reliable and comfortable for both tested persons and investigators. Hence, it appears to become a sophisticated approach to determine the GI.
Keywords: dospělí; C-Peptide; Female; LDL-cholesterol; Adult; Cholesterol, LDL; ženské pohlaví; Monitoring, Ambulatory; lidé; Blood Glucose; postprandiální období; Insulin; referenční hodnoty; Diet, Diabetic; krevní tlak; Glycated Hemoglobin A; dieta; Humans; Diet; glykemický index; Male; Reference Values; index tělesné hmotnosti; HDL-cholesterol; glykovaný hemoglobin; Postprandial Period; diabetická dieta; ambulantní monitorování; Glycemic Index; mužské pohlaví; C-peptid; Blood Pressure; Body Mass Index; inzulin; krevní glukóza; Glycated Hemoglobin; Cholesterol, HDL